Functionalized iron oxide supported on graphene oxide for hyperthermia application / Umar Ahmad Abulfathi - Umar Ahmad, Abulfathi (2021)
Cancer is one of the major causes of death globally (9.6 million in 2018). Magnetic hyperthermia therapy (MHT), a cancer therapy carried out at cellular level, has prospects in reducing these death rates. It is based on the concept that; magnetic nanoparticles (MNPs) deposited at cancer sites generate heat when exposed to an alternating current magnetic field and consequently destroy only the cancer cells by exploiting their vulnerability to heat. Thus, flaws like damage to healthy tissues and multidrug resistance associated with conventional treatments are avoided. As a challenge, using MNPs in their bare form can result in phagocytic capture, reducing their general tolerance in MHT. Henceforth, the surface of bare MNPs is modified. Unfortunately, such modification significantly reduces its heating efficiency, which implies a decline in MHT performance. This study curbed these challenges by fabricating a new magnetic hybrid nanostructure (MHNS); it mainly comprises Fe3O4 nanoparticle (FeNPs; one of the unique phases of MNPs), polyethylene glycol (PEG; a temperature-responsive surfactant) and graphene oxide (GO) nanoplatform. In a facile stagewise ex-situ approach, FeNPs was synthesized, functionalized with PEG (denoted as FAP), and finally grafted onto GO to form the MHNS. Optimizing the process by varying the composition loading reflects in the magnetic behavior; saturation magnetization values of 68.36, 60.89 and 40.76 emu/g were recorded for FeNPs, FAP and MHNS, respectively. All the VSM magnetization curves overlapped completely (S-shape), implying superparamagnetic behavior. Accordingly, these indicate successful functionalization and grafting. Interestingly, these indications also conform with the size increase (9.24, 11.97 and 12.25 nm, respectively) observed from XRD analysis and the detection of Fe, C, O and N elements by FESEM-EDX instrument. The presence of FeNPs in the synthesized products was affirmed by the consistent appearance of peculiar IR-band (around 550 – 578 cm-1 which was assigned to Fe – O vibration) in all the FTIR spectra. As aimed herein, the heating capacity of the iv MHNS quantified by specific absorption rate (SAR) should be efficient. It was observed to depend on concentration, composition, viscosity, magnetic field strength and for the first time pH. Grafting functionalized FeNPs (FAP) onto GO nanoplatform (which supports clustering the FAP) at 4:1 ratio improved the heating efficiency by 1.7-fold; dispensed 2-fold heat at simulated tumor microenvironment pH (4.5 – 6.98) compared to healthy cells microenvironment pH (> 7); timely generate significant amount of heat for prolonged period and reached 10 oC maximum temperature rise at 1.5 mg/mL, 15 kA/m and 316 kHz. These introduced a smart self-control attribute that could only yield the required thermal sensitization. Lastly, the SAR-viscosity relationship shows that SAR only drops with intense rise in heating medium viscosity (760-fold) and remains roughly constant at lower viscosities (ƞ < 34 mPa.s), an indication that the heating mechanism is dominated by Néel relaxation. This relationship implies that the MHNS can perform in complex media like lymph and Cerebro Spinal Fluid (ƞ < 6 mPa.s). These results pave the way for fabricating new MHT materials, efficient at lower concentrations and cellular level pH.